Hyperpigmented Nodular Dermatofibroma: Two Cases Report and Brief Literature Review - Hardianty, Andi; Djawad, Khairuddin; Wahab, Siswanto; Nurdin, Airin (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Dermatofibroma (DF) is a common benign skin tumor (Benign Fibrous Histiocytoma) that mostly affects the extremities with a tendency to occur more often in older females than males. It usually presents as a slow growing small brown dome shape papule on the extremities. DF has a chronic nature and can sometimes regresses spontaneously. Dermoscopy is essential in the evaluation of DF to help differentiate it with other skin tumors. The gold standard evaluation for diagnosis of DF is biopsy with histopathologic examination. Removal of DF is often due to cosmetic factors, with surgical excision being the preferred method for removal. DF has an excellent prognosis. CASE REPORT: We present two case reports of women with hyperpigmented nodules on the lower extremity. Dimple sign was positive. From dermoscopic study showed a pigment network and central white patch pattern. On histologic examination revealed proliferation of fibroblast such as spindle cells as a storiform pattern and hyperplastic epidermis with hyperpigmentation of the basal layer. Based on clinical features, dermoscopy and histopathological evaluation, the diagnosis of DF was established. Both patients were perform surgically excision and have a good result. CONCLUSION: Dermatofibroma is benign fibrous histiocytoma that represents one of the most common skin tumours. Nodular hyperpigmented dermatofibroma is a clinical variant of Dermatofibroma which can be treated with surgical excision with good prognosis.